The Amazing Aggregation Skills of the Red Flour Beetle - Davis, Brianna; Marshall, Jeremy (My University, 2018)
The Red Flour Beetle is a major pest of grain processing plants. They are commonly found in temperate areas, such as the southern parts of the United States. The beetles are usually reddish brown, with adults ranging about 1/8 of an inch in size. It's very common to find large numbers of Red Flour Beetles clumped together within infested grain (Baldwin and Fasulo, 2003). This dense clumping has caused speculation on whether this strange aggregation behavior is due to environmental factors or related to shared genetic traits. Scientists can look at the influence of genes on behavior by using a mathematical formula called a heritability estimate. Heritability estimates give information about how much of an impact genes have on a behavior in a certain environment (Khan Academy, 2018). Instinctive behavior is also connected to the genetic information, when best determines behavior when a species' environment varies little from generation to generation (Breed and Sanchez, 2010). This instinctive behavior theory correlated with the hypotheses, if you place Red Flour beetles with different genetic strains into an environment together then the Red Flour Beetles with similar genetic strains will aggregate together. While conducted the research which included placing different Beetles with different genetic strains into the same environment, and recording the data, the result supported the hypothesis and helped further prove the instinctive behavior that organisms possess when it comes to their genetic information. When using the graphs theory to analyze the data, the results showed that in the first day of observation, the largest percentage of interactions per group was for neither the genetic traits nor the environmental traits. However, when observing the second day the largest percentage of interactions per group was the genetic traits, helping to support the question of the different effects genetic and environmental traits have on the aggregation of Red Flour Beetles. The results seem to support the fact that genetic information is a major key in helping to create interactions between organisms of the same genetic strain, as well as bringing these interactions back to equilibrium when the population is shuffled. These finding are huge for the Animal Sciences and Industry field, by helping to prove that instincts and behavior coexist and are more significant than just an environmental change, when it comes to organisms. This research also helps to pinpoint different aggregation habits.
Keywords: Fall 2018